Cancer mortality of cadmium workers. - Elinder, C G (1985)
Several epidemiological studies of workers exposed to cadmium indicate an increased risk of lung and prostatic cancer. The increase is statistically significant in some of the studies but the SMR is greater than 100 in almost all. A cohort study of the mortality among 522 Swedish workers exposed to cadmium for at least one year in a nickel-cadmium battery plant support the earlier findings. The SMR for lung and prostatic cancer increased with increasing dose and latency but did not obtain statistical significance. A combination of all the available data from the most recent follow up of causes of death among cadmium workers in six different cohorts shows 28 cases of prostatic cancer (SMR = 162) and 195 cases of lung cancer (SMR = 121). This new analysis suggests that long term, high level exposure to cadmium is associated with an increased risk of cancer. The role of concomitant exposure to nickel needs further study.